Effect of Ethical Leadership and Motivation on Pro-Environmental Behaviors: Evidence from Thai Automobile Industry - Sihabudin Sihabudin (Universitas Hayam Wuruk Perbanas, 2021)
Despite extensive research on corporate sustainability, little is known about the factors that may instill employees taking part in sustainability initiatives. To address this gap, the main objective of this study is to identify factors that can enhance employees' pro-environmental behaviors that enable them to participate in sustainability initiatives. This study posits that leadership and motivation may influence employees to develop their pro-environmental behaviors through motivation. In order to test the hypothesis of the study, the partial least square–structural equation modeling (PLS-SEM) approach was used to examine data of 169 employees of the Thai automobile industry. The results show that ethical leadership significantly predicts employees' pro-environmental behaviors. In addition, employees' intrinsic motivation serves as a mechanism by partially mediating the relationship between ethical leadership and employees' pro-environmental behaviors. The study also investigates the relationship between extrinsic motivation with basic pro-environmental behaviors of employees, but no empirical support was found in this regard. This study recommends that organizations encourage employee intrinsic motivation to enhance their pro-environmental behaviors and focus on increasing their performance.